Cirrhosis is under‐recognised in patients subsequently diagnosed with hepatocellular cancer. Issue 5 (19th January 2016) - Walker, M.; El‐Serag, H. B.; Sada, Y.; Mittal, S.; Ying, J.; Duan, Z.; Richardson, P.; Davila, J. A.; Kanwal, F.
Summary: Background: Most clinical practice guidelines recommend screening for HCC in patients with cirrhosis. However, patients with compensated cirrhosis are often asymptomatic and may remain unrecognised for years. Aims: To determine the extent to which cirrhosis is unrecognised in a US Veteran population with HCC, and to evaluate the association between lack of cirrhosis recognition and stage of HCC at diagnosis. Methods: We reviewed the electronic medical records of a random sample of HCC cases diagnosed in the national Veterans Affairs system between 2005 and 2011. We conducted multivariable analyses adjusting for patients' demographics, comorbidity, aetiology of underlying disease and healthcare utilisation including HCC surveillance. Results: Of 1201 patients with HCC and cirrhosis, 24.6% had unrecognised cirrhosis prior to HCC diagnosis. Older patients [>65 years, odds ratio (OR) 2.32], African Americans (OR 1.93), patients with alcoholic or NAFLD liver disease (OR 1.69 and 4.77 respectively), HIV (OR 3.02), and fewer comorbidities (Deyo 0 vs. 3, OR 2.42) had significantly higher odds of having unrecognised cirrhosis than comparison groups. Furthermore, patients with unrecognised cirrhosis were 6.5 times more likely to have advanced stage HCC at diagnosis. The effect of cirrhosis recognition on HCC stage remained significant after adjusting for pre‐specified covariates (OR 3.37). Conclusions: In one quarter of patients, cirrhosis was unrecognised prior to HCC diagnosis, and this group was significantly more likely to have advanced stage HCC. These findings emphasise the importance of timely evaluation for cirrhosis in at‐risk populations as a critical step to improving outcomes for patients with HCC.